Comparative coenological examinations on pastures of the Great Hungarian Plain I.: Horse and cattle pasture near Hódmezővásárhely - Kiss, Tímea; Malatinszky, Ákos; Penksza, Károly (JOURNAL OF LANDSCAPE ECOLOGY, 2006)
Two groups of coenological relevés were prepared in 1997 and 2005 on sandy, alkali areas near Hódmezővásárhely town. Areas situated inside and near (0 to 50 meters far from) an animal husbandry farm belong to the first group. Coenological relevés gained from areas situated 50 to 150 meters far from intensively used areas belong to the second group. Data evaluation was made with considering naturalness state in case of habitats; and on the other hand, according to relative ecological factors of occurring species. A significant change in species composition could be detected. Particularly, deterioration of areas could be experienced. These negative processes are extremely heavy inside and near the animal husbandry farm. Even aggressive, invasive plant species occurred. Among dominant grass species, dominance relations and covering rate of disturbance tolerant Cynodon dactylon and Lolium perenne species have increased, caused partly by overgrazing and trampling as well. Farther from the farm, rate of degradation showed by vegetation has decreased compared to the areas closer to the farm, however, it has increased even on the farther area between the two time periods. During the preparation of management plans for the grasslands, these data should be considered at a higher rate in favour of preserving natural values, especially because the biggest population of nature protected Trifolium subterraneum lives in this area.
Keywords: grazing; overgrazing; trampling; alkali grassland; coenological examination